Study Of Raw Contracts in Electronic Contracts in The Digital Era Based on Indonesian Contract Law - Wendra, Ario Wendra (Strata Law Review, 2024)
Standard contracts in the digital era are made in the form of terms and conditions (terms of use) and electronic contracts (e-contracts) using digital signatures. As a contract user, you have no choice but to agree to the contract if you want to use the technology provider's facilities or refuse but cannot use the technology. There is no bargaining position or balance between technology providers and users. How is the Standard Contract Arrangement in Electronic Contracts in the Digital Age Based on Indonesian Contract Law? And how is the application of standard contracts in electronic contracts in the digital era based on Indonesian contract law? This research aims to study Raw Contracts in electronic contracts in the digital era based on Indonesian contract law. This study uses a normative juridical research method with secondary data consisting of primary, secondary, and tertiary legal materials. Standard Contract Arrangements in Electronic Agreements in the Digital Age Based on Indonesian Contract Law have not been regulated in detail. For this reason, it is necessary to make a regulation that explicitly regulates Electronic Standard Contracts and Contracts/agreements in general. This is based on the principle of Lex specialis derogat legion generali.